COLLABORATIVE SHARING-TASKS LEARNING FOR EARLY CHILDHOOD EDUCATION - Rosita Wondal; Farida Samad; Sasmayunita Sasmayunita (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aimed to describe the implementation of collaborative sharing-tasks learning on the ‘Occupations’ topic at Santo Yoseph Preschool Group B1 in Ternate. The students involved in this study were those registered in the 2018/2019 academic year. Data collection was performed using observation and documentation. In data analysis, Miles and Huberman interaction model was employed to describe the data qualitatively. The results of the study revealed that the implementation of collaborative sharing-tasks learning on “Occupations” implemented at Santo Yoseph Preschool Group B1 in Ternate was effective. Six groups of students were able to complete the tasks given by 76.92% through collaborative sharing-task learning. Therefore, it can be said that collaborative sharing-task learning can improve preschool students’ ability in understanding materials on ‘Occupations’.